Ecotoxicological assessment of soil microbial community tolerance to glyphosate - Allegrini, Marco (2015)
Glyphosate is the most used herbicide worldwide. While contrasting results have been observed related with its impact on soil microbial communities, more studies are necessary to elucidate the potential effects of the herbicide. Differences in tolerance detected by Pollution Induced Community Tolerance (PICT) approach could reflect these effects. The objective of the present study was to assess the tolerance to glyphosate (the active ingredient and a commercial formulation) of contrasting soils with (H) and without (NH) history of exposure. The hypothesis of a higher tolerance in H soils due to a sustained selection pressure on community structure was tested through the PICT approach. Results indicated that tolerance to glyphosate is not consistent with previous history of exposure to the herbicide. Studies of community structure based on Denaturant Gradient Gel Electrophoresis (DGGE) and Quantitative Real Time PCR (Q-PCR) showed that composition and abundance of bacteria, respectively, did not differ significantly between H and NH soils, in accordance with PICT results. Consequently, the lack of significant differences in tolerance in most cases could be partially explained by a similar community structure. This is, to our knowledge, the first report of PICT approach with glyphosate examining tolerance at soil microbial community level. Future culture-independent analysis focused on specific groups of microorganisms instead of whole microbial communities could be important to provide stronger evidences supporting our results and conclusions.